Accountability in malaria prevention and treatment programmes: a review of current challenges. (April 2017) - Danhoundo, Georges; Wiktorowicz, Mary; Gorman, Rachel
Abstract: Background: Sound governance is a fundamental tenet of financial aid programmes for malaria prevention and treatment in low-income countries, yet their limited effectiveness in reducing the prevalence of malaria suggests weaknesses in the underlying accountability frameworks. Despite heightened global attention since the Roll Back Malaria Partnership was launched in 1998, 214 million new cases and 438 000 deaths due to malaria were reported in 2015. Millions of people lack access to malaria prevention and treatment services in Africa, where 80% of malaria deaths occur. We aimed to clarify accountability frameworks and mechanisms that underlie malaria prevention and treatment programmes in sub-Saharan African countries. Methods: To clarify accountability mechanisms in maternal and child health malaria programmes in Benin, Burkina Faso, and Mali, we reviewed policy reports and studies published between Jan 1, 2000, and Aug 1, 2016, and undertook semi-structured key informant interviews with national ministries of health, non-governmental organisations, WHO, and the Global Fund to fight AIDS, Tuberculosis and Malaria. We triangulated results with findings from interviews with local health professionals and pregnant women done in 2015–16. We analysed recorded and transcribed interviews through framework analysis using NVivo software. Findings: We included 15 reports, 60 studies, and 118 individual interviews in analysis. Our analysis of accountability frameworks identified general indicators of programme implementation success such as antenatal physician visit attendance. However, important limitations in programmes were also identified. These included insufficient delineation and measurement of operational aspects of programme implementation and a lack of specific measures within local health systems used to ensure target groups' access to malaria prevention and treatment. The manner in which preventable health system deficiencies, such as medication shortages, were to be addressed and evaluated were absent from current accountability frameworks. We also noted that global accountability measures were "glocalised" by national actors, since policy adoption was infused with local customs and practices. Interpretation: National health leadership is a key driver in successful health outcomes. Changes in accountability frameworks to foster sound national health governance and leadership could support development of a more comprehensive array of practices to specifically address challenges in programme implementation, including how preventable local health system deficiencies will be alleviated to meet programme goals. Country-specific programme goals should be harmonised with the goals of national health leaders. Funding: York University, ON, Canada.